Effects of Job Satisfaction and Organizational Commitment on Nurse Retention: A Systematic Review - Agit Pratama Putra; Kusnanto Kusnanto; Slamet Riyadi Yuwono (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2020)
Introduction: Nurse turnover is a problem linked to low job satisfaction and organizational commitment; therefore, appropriate nurse retention strategy from nursing managers and human resource is needed. This study aims to explain the effects of job satisfaction and organizational commitment on nurse retention. Methods: This systematic review uses registration protocol from The Joanna Briggs Institute Guideline as a guide in the quality assessment of the summarized studies. Studies using the PICOS Framework were sourced from the following databases: Scopus, ScienceDirect, PubMed, EBSCOhost, JSTOR, SAGE, and ProQuest, published between 2010-2020, the study design was limited to cross-sectional, quasi-experiment, and randomized control trials. The feasibility study assessment used the Joanna Briggs Institute Critical Appraisal; the search keywords were adjusted according to the Medical Subject Headings and Boolean operators. The selection results are displayed in the PRISMA flow chart. Results: The initial search of the entire database found 8059 articles, then several duplication screenings of titles  30 articles were extracted. A feasibility assessment was carried out so that the remaining 25 articles were divided into two themes, namely job satisfaction and organizational commitment, each of which can affect nurse retention. According to this study, organizational commitment has a broader dimension of job satisfaction. Conclusion: Job satisfaction and organizational commitment have an influence on nurse retention; both are of concern for nurse managers to create effective nurse retention strategy.